Constructing Space, Changing Reality of Israel through Film Journal for Religion, Film and Media - Milja Radovic (Journal for Religion, Film and Media, 2019)
This paper investigates the ways in which filmmakers through cinematic space frame reality, mediating the issues of conflict and reconciliation, religion and identity(ies) within Israel. Cinematic space depicts and expresses borders through elements of film language, such as mise-en-scène, montage and the disruption of temporal reality. By (re) framing meanings cinema questions existing socio-political realities, and their impact on the individual or whole communities. The microcosmic realities which constitute different communities within Israel's wider socio-political reality are built and confronted through the cinematic space. The cinema thus becomes a site through which existing realities are reflected and new realities are constructed, opening up possibilities for transformation. In other words, how film frames an 'alternative reality(ies)' is a question related to the construction of space, which will be addressed in this paper. The paper focuses on two films: WEST OF THE JORDAN RIVER (Amos Gitai, 2017) and GEULA (Joseph Madmony, Boaz Yehonatan Yacov, 2018). I juxtapose these two diametrically different films in order to assess the ways in which the cinematic space functions as a direct site for negotiating the identities, religious belonging, and the different communities' relation to the geographical space of Israel. The analysis of these two films aims to 'sharpen the focus' on cinematic space as a continuum in which such complex realities are expressed, renegotiated, and transformed.